2016
DOI: 10.1007/s11069-016-2259-3
|View full text |Cite
|
Sign up to set email alerts
|

Future typhoon and storm surges under different global warming scenarios: case study of typhoon Haiyan (2013)

Abstract: The present work evaluates potential future typhoon and storm surges around the islands of Samar and Leyte in the Philippines taking into account monthly mean sea surface temperatures, atmospheric air temperature, and relative humidity (hereafter, SST, AAT, and RH) from MIROC5 according to four scenarios proposed by IPCC AR5. Supertyphoon Haiyan (2013), which caused catastrophic damage to coastal areas in the Philippines due to its high winds and storm surge, was used as the case study storm given that it was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 65 publications
(74 reference statements)
0
32
0
Order By: Relevance
“…If using the maximum wind speed to estimate cyclone's kinetic energy at peak to a first order, the corresponding square of maximum wind speed of a ''category 6'' (160-185 knots) TC would be 131-175% higher than a ''category 5'' TC of 140 knots.) It is intriguing to compare the situation for these two ''Category 6'' TCs Lander et al, 2014;Comiso et al, 2015;Shu et al, 2015;Wada, 2015;Foltz and Balaguru, 2016;Kimberlain et al, 2016;Nakamura et al, 2016;Takagi et al, 2016;Fu et al, 2017;Rogers et al, 2017] over the two sides of the Pacific basin, i.e. Hurricane Patricia to the Mexico versus suppertyphoon Haiyan to the Phillippines.…”
Section: Introductionmentioning
confidence: 99%
“…If using the maximum wind speed to estimate cyclone's kinetic energy at peak to a first order, the corresponding square of maximum wind speed of a ''category 6'' (160-185 knots) TC would be 131-175% higher than a ''category 5'' TC of 140 knots.) It is intriguing to compare the situation for these two ''Category 6'' TCs Lander et al, 2014;Comiso et al, 2015;Shu et al, 2015;Wada, 2015;Foltz and Balaguru, 2016;Kimberlain et al, 2016;Nakamura et al, 2016;Takagi et al, 2016;Fu et al, 2017;Rogers et al, 2017] over the two sides of the Pacific basin, i.e. Hurricane Patricia to the Mexico versus suppertyphoon Haiyan to the Phillippines.…”
Section: Introductionmentioning
confidence: 99%
“…However, as Batasan and Ubay (see picture on page 7), until recently, have been using coral stones as filling materials, examining the impact of rampant coral mining on the long-term physical viability of the islands is needed. A survey of a mined reef section in Batasan revealed a live hard coral cover of less than 10%, with a further 30% of dead coral with algae, indicating that the area is already severely degraded (Jamero et al 2017 Also, extreme events such as typhoons and droughts often are perceived to constitute a limit of adaptation, potentially driving mass migration even in the short term (Nakamura et al 2016, Fletcher and Richmond 2010, Yamamoto and Esteban 2014. However, this study found that the island communities of Tubigon have remained in their homes despite experiencing several typhoons since the 2013 earthquake, and a 4-month long dry spell in 2016.…”
Section: A Physical or Biological Limitmentioning
confidence: 99%
“…Among the 10 typhoons landing in Vietnam in 2013, Cat. 5 Haiyan in early November turned into one of the world strongest recorded tropical cyclones [23].…”
Section: Typhoonsmentioning
confidence: 99%